In honor of broken things - Acampora, Paul (Dial Books for Young Readers, 2022)
Oscar has just lost his beloved younger sister to cancer, Noah is a genius who has been homeschooled all his life but has decided he wants to go to middle school, Riley is an artist who has just moved back to West Beacon with his mother after she was held up at gun point--they are three unlikely friends with troubles in their lives, but when they meet in their middle school pottery class, they begin to learn how to piece their lives back together again.